Food safety and GM crops -- implications for developing-country research: food safety in food security and food trade - Cohen, Joel I.; Quemada, Hector; Frederick, Robert J. (International Food Policy Research Institute, 2003)
In the developing world the approval and cultivation of genetically modified (GM) crops is largely limited to the commercial production of insect-resistant cotton in Argentina, China, India, Mexico, and South Africa.... Approvals of GM crops used for food or feed lag far behind cotton... This gap in approvals is unfortunate, because crop biotechnology, appropriately applied, has the potential to address key production constraints affecting resource-poor farmers. Currently, important public- and private-sector research is underway to help meet the productivity needs of these farmers. -- from Text